The star function for meromorphic functions of several complex variables - Abi-Khuzam, Faruk; Bertrand, Florian; Della Sala, Giuseppe (Complex variables and elliptic equations, 2019)
We define an analogue of the Baernstein star function for a meromorphic function f in several complex variables. This function is subharmonic on the upper half-plane and encodes some of the main functionals attached to f. We then characterize meromorphic functions admitting a harmonic star function.